Pengaruh Komunikasi Dan Budaya Organisasi Terhadap Kepuasan Kerja Pegawai Pada Dinas Pariwisata Kota Bima - Muhammad Nauval; Muhammad Yusuf (Jurnal Riset Ekonomi dan Akuntansi, 2023)
This research aims to determine the influence of communication and organizational culture on employee satisfaction at the Bima City Tourism Office. Data collection techniques in this research are questionnaires, observation and literature study. The sample in this study was 31 ASN with the sampling technique being purposive sampling. The data analysis technique uses multiple linear regression. The research results show that both partially and simultaneously, communication and organizational culture have a significant influence on employee job satisfaction at the Bima City Tourism Office.